2012
DOI: 10.1016/j.foodchem.2011.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Pleurotus ostreatus mushrooms with selenium in coffee husks

Abstract: Pleurotus ostreatus fungus forms an edible mushroom that possesses important nutritional and medicinal properties. Selenium (Se) is essential to human diets and it is in low concentration in the soil, and consequently in food. P. ostreatus was grown in coffee husks enriched with various concentrations of sodium selenite. The biological efficiency of P. ostreatus was affected by the addition of high concentrations of Se. The highest level of Se absorption was obtained by adding 51 mg kg 1 of sodium selenite. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 27 publications
(31 reference statements)
7
75
1
8
Order By: Relevance
“…145.462.9 vs 5.060.46, followed by P. ostreatus, P. sajorcaju, P. fossulatus and P. citrinopileatus (Table 1). The extent of accumulation was higher than the selenium concentration reported in the case of Pleurotus eryngii (4.6 and 9.3 mg Se/g dw) cultivated on substrates supplemented with 5.0 and 10.0 mg Se/g dw of sodium selenite respectively (32), Similar results have recently been reported by da Silva et al (27), where selenium accumulation in P. ostreatus was found to be higher (57.6 mg Se/g dw) than our observations (44.3 mg Se/g dw) with the same species when cultivated on Se-enriched coffee husks supplemented with 3.2 mg/kg of sodium selenite. Total selenium content in enriched L. edodes and Ganoderma lucidium was found to be 46 mg Se/g and 72 mg Se/g respectively (33,34), which lies within the range observed in the present study.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…145.462.9 vs 5.060.46, followed by P. ostreatus, P. sajorcaju, P. fossulatus and P. citrinopileatus (Table 1). The extent of accumulation was higher than the selenium concentration reported in the case of Pleurotus eryngii (4.6 and 9.3 mg Se/g dw) cultivated on substrates supplemented with 5.0 and 10.0 mg Se/g dw of sodium selenite respectively (32), Similar results have recently been reported by da Silva et al (27), where selenium accumulation in P. ostreatus was found to be higher (57.6 mg Se/g dw) than our observations (44.3 mg Se/g dw) with the same species when cultivated on Se-enriched coffee husks supplemented with 3.2 mg/kg of sodium selenite. Total selenium content in enriched L. edodes and Ganoderma lucidium was found to be 46 mg Se/g and 72 mg Se/g respectively (33,34), which lies within the range observed in the present study.…”
Section: Resultssupporting
confidence: 82%
“…The selenium concentration in unenriched substrate was found to be higher (1.960.8 mg Se/g dw) than in the earlier reports which lay in the range of 0.09-0.19 mg Se/g dw in different substrates (27,28) and the resulting concentrations in fruiting bodies were in the range of 2.9-5.2 mg Se/g dw, which is almost comparable to the range (0.12-3.4 mg Se/g dw) of selenium conentartion in wild and edible species of Pleurotus (29)(30)(31). The fruiting bodies (first flush) of all species of Pleurotus harvested from Se-rich wheat straw containing a total Se concentration of 24.060.2 mg Se/g dw, were noted to accumulate significantly higher (p,0.0001) selenium as compared to control mushrooms grown on control wheat straw (1.960.8 mg Se/g dw).…”
Section: Resultscontrasting
confidence: 73%
“…The use of this residue as substrate for mushroom cultivation seems to be an interesting strategy to add economic value to this residue and prevent environmental pollution. Many studies successfully reported production of mushrooms in sterilized coffee husk (Fan et al, , 2003Dias et al, 2003;da Silva et al, 2012). However, in South America, mushrooms are an expensive food, especially when compared with meat, making its commercialization difficult, thus justifying investigations of cheap methods to cultivate mushrooms in coffee husk.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to give a destination to this agro-industrial residue, studies have been made to use coffee husk as substrate for mushroom production (Fan et al, 2003;Dias et al, 2003;da Silva et al, 2012). Furthermore, *Corresponding author: E-mail: mkasuya@ufv.br.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of toxic compounds (e.g., caffeine found in the coffee husk) can inhibit or decrease P. ostreatus growth (Pandey et al, 2000;Fan et al, 2003). However, this problem seems to be attenuated by performing a prior boil of the substrate (Houdeau et al, 1991;da Silva et al, 2012;de Assunção et al, 2012). Therefore, substrates should be carefully selected to favor fungal growth.…”
Section: Discussionmentioning
confidence: 99%